2020
DOI: 10.5469/neuroint.2019.00241
|View full text |Cite|
|
Sign up to set email alerts
|

Transcarotid Mechanical Thrombectomy for Embolic Intracranial Large Vessel Occlusion after Endovascular Deconstructice Embolization for Carotid Blowout Syndrome

Abstract: Carotid blowout syndrome (CBS) is a fatal complication of head and neck cancer. Endovascular treatment, particularly deconstructive embolization, is effective for CBS, but it might result in thromboembolic events. We report the case of a 57-year-old man with underlying recurrent head and neck cancer who had CBS. The patient received endovascular embolization of the right internal, external, and common carotid arteries. Right internal carotid artery to middle cerebral artery embolic occlusion was noted immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The authors reported their successful bailout experience of transcarotid mechanical thrombectomy of an intracranial embolic occlusion after parent vessel sacrifice due to an impending carotid blowout syndrome. 1 Endovascular management of carotid blowout syndrome is one of the most urgent experiences for a neurointerventionist who must make fast and critical decisions under suboptimal conditions. The patient is usually chronically ill and may be vitally unstable due to the bleeding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported their successful bailout experience of transcarotid mechanical thrombectomy of an intracranial embolic occlusion after parent vessel sacrifice due to an impending carotid blowout syndrome. 1 Endovascular management of carotid blowout syndrome is one of the most urgent experiences for a neurointerventionist who must make fast and critical decisions under suboptimal conditions. The patient is usually chronically ill and may be vitally unstable due to the bleeding.…”
mentioning
confidence: 99%
“…2 Intra-procedural embolic stroke from migration of the embolic materials or thrombus formed during deconstructive treatment can be another potential complication as seen in this report. 1 Similar to the carotid stump syndrome, a thrombus formed from stasis of blood in the internal carotid artery (ICA) with distal migration by antegrade/collateral flow or migration of thrombus formed in the common carotid artery/external carotid artery (ECA) through ECA-ICA anastomosis can be potential mechanisms. 1,5 For prevention of this complication, ICA sacrifice from the level proximal to the ophthalmic artery to the site of carotid rupture may be considered to prevent potential petrocavernous ECA-ICA collateral flow related to thrombus migration.…”
mentioning
confidence: 99%